MnSn(OH)6 derived Mn2SnO4@Mn2O3 composites as electrode materials for high-performance Supercapacitors. (April 2022) - Barai, Hasi Rani; Rahman, Md. Mahbubur; Adeel, Muhammad; Joo, Sang Woo
Highlights: MnSn(OH)6 (MSH) derived Mn2 SnO4 @Mn2 O3 (MSO@MO) nanostructure synthesized for the first time. MSO@MO exhibited isolated nanoparticle and nanorod morphologies, respectively. The MSO@MO outperformed the capacitive performance of MSH. The MSO@MO electrode delivered high capacitance, energy density, and good cycling stability. Abstract: This research demonstrated the synthesis of Mn2 SnO4 and Mn2 O3 (MSO@MO) with isolated nanoparticle and nanorod morphologies, respectively, derived from MnSn(OH)6 (MSH) for electrochemical supercapacitor applications. The MSH was synthesized using a simple solution process and converted to MSO@MO composites by thermal annealing with good crystallinity, purity with the MSO and MO ratio of 1:0.46. The MSH and MSO@MO-modified Ni foam electrodes exhibited the specific capacitance (Cs ) of 1000.86 and 1197.75 F/g, respectively, at 10 mV/s, and 512.0 and 660.0 F/g, respectively, at 0.4 A/g. The enhanced Cs value and high energy density (22.91 Wh/Kg at 0.4 A/g) of the MSO@MO were attributed to the synergistically improved surface area, decreased charge-transfer resistance (Rct ) at the electrode/electrolyte interface, and a high degree of charge intercalation/deintercalation into the tunnels of MSO and MO. The MSO@MO electrode exhibited excellent electrochemical cycling stability with the capacity loss of only 5.5% after 5000 charge/discharge cycles. Graphical abstract: Image, graphical abstract